Optimalisasi Strategi Manajemen dalam Meningkatkan Daya Saing Apotek Pro LoMedika - Fairuz Bachmid; Erliany Syaodih; Yen Emawati (Yayasan Literasi Sains Indonesia, 2025)
This study aims to analyze the management strategies applied at Apotek Pro LoMedika Manado in order to increase competitiveness in the midst of the tight retail pharmaceutical industry. The background of this research is the condition of the pharmacy which after two years of operation has not been able to finance its own operations and faces competition from several adjacent pharmacies. This research uses a qualitative method with a case study approach through direct observation, in-depth interviews with managers, pharmacists, and pharmacy owners, and review of financial statements for the period January 2023-December 2024. The analysis was carried out using a SWOT framework that maps strengths, weaknesses, opportunities, and threats, then determines the right strategy to deal with market dynamics. The results showed that Pro LoMedika Pharmacy has a strategic position with great opportunities, but faces internal challenges in the form of suboptimal financial and inventory management. From the results of the SWOT analysis, the pharmacy is in quadrant I which is recommended to use an aggressive strategy, which maximizes internal strengths and external opportunities. These strategies include increasing product variety, stock control, optimizing services through POS technology, and collaborating with doctors and suppliers to get competitive prices and credit for goods. In conclusion, the implementation of more structured strategic management is able to become the basis for increasing the competitiveness and sustainability of pharmacy operations in the future.